2023
DOI: 10.3389/fmicb.2023.1156061
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B resistance correlates with increased fitness in vitro and in vivo in Leishmania (Mundinia) martiniquensis

Abstract: Amphotericin B (AmpB) deoxycholate is the available first-line drug used to treat visceral leishmaniasis caused by Leishmania (Mundinia) martiniquensis, however, some cases of AmpB treatment failure have been reported in Thailand. Resistance to drugs is known to affect parasite fitness with a potential impact on parasite transmission but still little is known about the effect of resistance to drugs on L. martiniquensis. Here we aimed to gain insight into the fitness changes occurring after treatment failure or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Aspergillus species demonstrated a 1.09-fold increase in resistance while other filamentous fungi exhibited a 1.07-fold increase in resistance to natamycin per annum [135]. Resistance of fungi to other polyene macrolide antifungals including Amphotericin B has also been reported in other studies [39] [140] [141] [142] [143]. A study in the United States also reported high fluconazole-resistant candida species [143].…”
Section: Examples Of Fungi Resistant To Antifungal Agentsmentioning
confidence: 77%
“…Aspergillus species demonstrated a 1.09-fold increase in resistance while other filamentous fungi exhibited a 1.07-fold increase in resistance to natamycin per annum [135]. Resistance of fungi to other polyene macrolide antifungals including Amphotericin B has also been reported in other studies [39] [140] [141] [142] [143]. A study in the United States also reported high fluconazole-resistant candida species [143].…”
Section: Examples Of Fungi Resistant To Antifungal Agentsmentioning
confidence: 77%
“…Using other media such as the biphasic NNN with antibiotics and performing serial dilution may allow to obtain pure promastigote cultures easily. Recently, our study regarding Amphotericin B (AmpB)-resistant L. martiniquensis parasites has suggested that the resistant strains could be more efficiently transmitted and maintained in asymptomatic hosts longer than susceptible ones (Mano et al, 2023). Thus, the isolation of parasites from is required to not only the vector competence of the insects but also the prevalence of the AmpB-resistant phenotype parasites in natural insect populations.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of autochthonous leishmaniasis in Thailand is increasing and new cases continue to be reported (Anugulruengkitt et al, 2022;Srivarasat et al, 2022), but the natural vectors that are responsible for the transmission of the disease remain unknown. Moreover, more relapse cases caused by L. martiniquensis have been reported (Srivarasat et al, 2022;Mano et al, 2023). Various species of sand flies are known as natural vectors of Leishmania parasites in the subgenera Viannia and Leishmania (Cecílio et al, 2022).…”
Section: Introductionmentioning
confidence: 99%